Development of a Fully Automated Microfluidic Electrochemical Sensor on the ESSENCE Platform for Rapid Detection of Single-Stranded DNA - Niranjan Haridas Menon; Maryom Rahman; Sagnik Basuray (Proceedings)
This study presents a fully automated microfluidic electrochemical sensor for the detection of single-stranded DNA (ssDNA) on the ESSENCE platform. The sensor utilizes functionalized single-walled carbon nanotubes (SWCNTs) with short ssDNA strands immobilized through EDC-NHS coupling, placed between non-planar interdigitated electrodes. The detection process involves sequential flow of a background electrolyte and redox probe through the microfluidic channel before introducing the target DNA solution. The same solution is then circulated to enhance selectivity by removing non-specifically bound targets. Electrochemical impedance signals are acquired after the initial and final flow steps, utilizing changes in impedance spectra to quantify target DNA concentration. To streamline complex flow steps and eliminate manual interventions, the system integrates a fully automated fluid control system with syringe pumps, valves, and pressure sensors. Electrochemical impedance spectroscopy (EIS) data is acquired using the Analog Discovery 2 USB oscilloscope, and LabVIEW automation ensures a seamless transition from sample introduction to data acquisition. The transducer material’s flow-through design enables efficient differentiation between different degrees of base pair mismatches, extending applicability to single nucleotide polymorphisms. The system exhibits high sensitivity, detecting single-stranded DNA at concentrations as low as 1 fM within a rapid 15-min detection time. Its compact design and automated data acquisition make it a promising candidate for point-of-care biomolecule sensing, including antigens and toxins. Future applications involve functionalizing SWCNTs with relevant antibodies to enhance the platform’s capabilities for detecting a diverse range of target molecules in clinical settings.